The interdependence of functional and dynamic stability of the 16-18 years old basketball players - A pilot study - Slomka, K. J.; Furmanek, M. P.; Litkowycz, R.; Srczepanska, J.; Juras, G. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
We aimed to determine the interdependence between functional and dynamic stability of young basketball players. Nineteen, young basketball players took part in the experiment. They were tested with Y Balance TestTM for functional stability and with *Drift protocol" of the Optojump Next System for dynamic stability. The correlation analysis showed interdependencies between functional balance testing and dynamic performance. The Composite Reach Score is highly associated with individual leg jump power. Also there are significant dependencies between jumping stability in AP and ML planes and reach distances in specified directions. Other significant correlations indicate the need for conducting functional testing in parallel with dynamic trials in order to achieve wider picture of the athletes perforrnance.